P.096 A single institution experience with 217 average risk patients undergoing carotid angioplasty and stenting in the post CREST era, a real life experience. (17th June 2016) - Drake, B; Alizadeh Vakili, N; Sarma, D; Bharatha, A; Marotta, T; Montanera, W; Chiu, A; Spears, J
Abstract : Background: The CREST trial remains the most influential study regarding choice of treatment modality for carotid revascularization in the modern era. The effect of the CREST trial on patient outcomes and changes to clinical practice are yet to be fully elucidated.Methods : We report a cohort of 217 consecutive symptomatic average risk patients undergoing CAS at St. Michael's Hospital, between 2010 and 2016. Outcome measures were stroke, MI and death at 30 days post procedure. Of the 217 patients, 42 were above the age of 75 (19%).Results: The 30-day combined stroke, MI and death outcome for all patients was 4.1%. One death occurred (0.46%) in a patient who suffered an MI. One disabling stroke (0.46%) and 3 mild strokes (1.38%) with full recovery by 6 months occurred. Overall 4 patients suffered an MI (1.84%).Conclusions: As a result of the CREST trial in our single institutional experience there has been a clear migration to treating average risk patients using CAS, a treatment previously reserved for high risk patients. In this average risk cohort we report favourable outcomes when compared to the CREST trial as well as the firmly established benchmarks for CEA complications derived from the NASCET trial.